Incidence of Side Effects from Levodopa during the Introduction of Treatment. Issue 5743 (30th January 1971) - Godwin-Austen, R. B.; Frears, C. C.; Bergmann, S.
Abstract : Twenty patients with Parkinsonism were investigated in order to establish whether the gradual introduction of treatment with levodopa allows a higher dose to be tolerated than can be achieved if treatment is introduced rapidly. No indication was obtained that slow introduction of treatment offers an advantage in maximum tolerated dose, and patients aged 65 and over responded similarly in this respect to those under 65. The maximum tolerated dose is slightly lower in the elderly patient. The incidence of the different side effects does not appear to be affected by the rate of increasing the dose of levodopa.